Managing High Frequency of Ambulance Calls in Hospitals: A Systematic Review - Alruwaili A; Alanazy A; Alanazi TM; Alobaidi N; Almamary AS; Faqihi BM; Al Enazi FH; Siraj R; Almukhlifi Y; Al Nufaiei ZF; Alsulami M (Dove Medical Press, 2024)
Abdullah Alruwaili,1- 4 Ahmed Alanazy,1- 3 Turki M Alanazi,1- 3 Nowaf Alobaidi,1- 3 Ahmad Saleh Almamary,1- 3 Bandar M Faqihi,1- 3 Fahad H Al Enazi,1- 3 Rayan Siraj,5 Yasir Almukhlifi,6,7 Ziyad F Al Nufaiei,6,7 Maher Alsulami6,7 1College of Applied Medical Sciences, King Saud bin Abdulaziz University for Health Sciences, Al-Ahsa, Saudi Arabia; 2King Abdullah International Medical Research Center, Al-Ahsa, Saudi Arabia; 3Ministry of National Guard- Health Affairs, Al Ahsa, Saudi Arabia; 4School of Health: Faculty of Medicine and Health, University of New England, Armidale, New South Wales, Australia; 5Department of Respiratory Therapy, College of Applied Medical Sciences, King Faisal University, Al-Hasa, Saudi Arabia; 6College of Applied Medical Sciences, King Saud bin Abdulaziz University for Health Sciences, Jeddah, Saudi Arabia; 7King Abdullah International Medical Research Center, Jeddah, Saudi ArabiaCorrespondence: Maher Alsulami, Department of Emergency Medical Services, College of Applied Medical Sciences-Jeddah, King Saud bin Abdulaziz University for Health Sciences, Mail Code 6610, P.O.Box.9515, Jeddah, 21423, Saudi Arabia, Tel +966501596230 Ext 46087, Email alsulamim@ksau-hs.edu.saBackground: This study addresses the critical issue of high-volume emergency calls in hospitals, focusing on the strain caused by frequent caller patients on ambulance services. The aim was to synthesize various management methods for handling high-frequency hospital calls.Methods: The systematic review was conducted following the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) guidelines and guided by the Cochrane Handbook for systematic reviews. Inclusion criteria encompassed studies focusing on the management of emergency departments in hospitals, exploring various medical conditions requiring ambulance attention, and reporting on the impact of a high volume of ambulance calls on hospitals. Databases including PubMed, Web of Science, and Google Scholar were searched from January 1, 2005, to May 1, 2022. The quality of included studies was assessed using the Critical Appraisal Skills Programme (CASP) Checklist.Results: Out of 2390 identified citations, 18 studies met the inclusion criteria. These studies, from 12 countries, presented diverse methods categorized into country policy-based management, modeling approaches, and general strategies. Key findings included the effectiveness of risk stratification models and community-based interventions in managing high call frequencies and improving patient care. Our review identified effective strategies such as risk stratification models and community-based interventions, which have shown significant impacts in managing high call frequencies, aligning closely with our objective. These approaches have been pivotal in reducing the burden on emergency services and improving patient care.Conclusion: The study synthesizes effective management methods for high-frequency ambulance calls, including predictive modeling and community interventions. It highlights the need for multi-faceted management strategies in different healthcare settings and underscores the importance of continued research and implementation of these methods to improve emergency service efficiency.Keywords: systematic review, ambulance calls, emergency services